ANALISIS PERAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI MELALUI DISIPLIN KERJA PADA KANTOR DINAS PARIWISATA KOTA MAKASSAR - Hendra Gunawan (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2026)
This study aims to analyze the role of organizational commitment in influencing employee performance by considering work discipline as a mediating variable at the Makassar City Tourism Office. The study employed a quantitative approach, employing a survey. Data were collected through questionnaires distributed to employees and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results indicate that organizational commitment has a positive effect on employee performance. In addition, organizational commitment also positively influences work discipline. Work discipline is found to have a positive effect on employee performance and acts as a mediating variable in the relationship between organizational commitment and employee performance. These findings suggest that stronger organizational commitment fosters greater work discipline, thereby improving employee performance. This study contributes to the development of human resource management literature in the public sector and provides practical implications for government organizations in improving employee performance through strengthening organizational commitment and fostering a culture of work discipline.